The effect of tizanidine on maximal electroshock seizures (MES) in mice - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1999)
Tizanidine, an alpha-2 adrenergic agonist, is a centrally active muscle relaxant and a spasmolytic drug. The aim of our study was to investigate the activity of tizanidine on maximal electroshock seizures (MES) in mice. In the first part of the study, convulsive current 50 (CC 50) value to produce seizures was found. Then, tizanidine was given intraperitoneally (IP) at the doses of 0.5, 1, and 2 mg/kg, and orally (PO) at the doses of 5, 10, 20, 40 mg/kg. We found that tizanidine at the doses of 1 and 2 mg/kg IP and 40 mg/kg PO caused a significant protection against MES. In the second part of the study, after pretreatment with yohimbine, an alpha-2 adrenergic receptor blocker, at the dose of 2 mg/kg, anticonvulsant effect of tizanidine is diminished. We concluded that the mode of action of the anticonvulsant effect of tizanidine may be mediated by the central alpha-2 adrenergic receptors. (C) 1999 Elsevier Science Inc. All rights reserved.
Keywords: tizanidine; maximal electroshock seizures; mice; yohimbine; alpha-2 adenergic; receptor; MUSCLE-RELAXANT; ANTAGONISTS